Pengaruh Biota Plus Dan Pupuk Organik Cair Limbah Ternak Kerbau Terhadap Pertumbuhan Seledri (Apium graveolens L.) Dengan Teknik Budidaya Hidroponik - Berlian Zetikarya Haryati (AgroSainT, 2021)
Research on the Effect of Biota Plus and Liquid Organic Fertilizer from Buffalo Livestock Waste on the Growth of Celery (Apium graveolens L.) with Hydroponic Cultivation Techniques, the research was conducted in Mentirotiku Village, Rantepao District, North Toraja Regency in March-June 2020. concentration of Biota Plus and POC of Buffalo Waste that are appropriate for the growth of Celery Plants. This research was a factorial experiment with 2 (two) factors arranged in a randomized block design (RBD). Factor 1 was Biota Plus consisting of three treatment levels, namely B1 = 15 ml/l water, B2 = 30 ml/l water, B3 = 45 ml/l water, while factor 2 was buffalo waste liquid organic fertilizer consisting of four treatment levels, namely P0 = 0 ml/l water, P1 = 2 ml/l water, P2 = 4 ml/l water, P3 = 6 ml/l water. The results showed that the Biota Plus 45 ml/l water treatment gave the best results on leaf blade height, number of tillers, root volume, and fresh weight. Treatment of POC Buffalo Livestock Waste 4 ml/I water gave the best results on plant height, number of leaves, number of tillers, root volume, and fresh weight on growth and production of celery plants. The combination of POC Biota Plus 45 ml/l water and POC Buffalo Waste 4 ml/l water gave the best effect on plant height, number of tillers, root volume, and plant fresh weight.